Adult height, coronary heart disease and stroke: a multi-locus Mendelian randomization meta-analysis - Nüesch, Eveline Bettina; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; März, Winfried (International journal of epidemiology, 2016)
Abstract. Background: We investigated causal effect of completed growth, measured by adult height, on coronary heart disease (CHD), stroke and cardiovascular t
Gesehen am 28.03.2019
Advance Access Publication Date: 15 May 2015